Molecular insights into STAT1a protein in rohu (Labeo rohita): unveiling expression profiles, SRC homology domain recognition, and protein-protein interactions triggered by poly I: C - Das, Basanta Kumar; Panda, Soumya Prasad; Pradhan, Smruti Priyambada; Raut, Subhashree Subhasmita; Kumari, Mala; Meena, Dharmendra Kumar (Frontiers in Immunology, 2024)
Introduction STAT1a is an essential signal transduction protein involved in the interferon pathway, playing a vital role in IFN-alpha/beta and gamma signaling. Limited information is available about the STAT protein in fish, particularly in Indian major carps (IMC). This study aimed to identify and characterize the STAT1a protein in Labeo rohita (LrSTAT1a). Methods The full-length CDS of LrSTAT1a transcript was identified and sequenced. Phylogenetic analyses were performed based on the nucleotide sequences. The in-vivo immune stimulant poly I: C was used to treat various tissues, and the expression of LrSTAT1a was determined using quantitative real-time polymerase chain reaction (qRT-PCR). A 3D model of the STAT1a protein was generated using close structure homologs available in the database and checked using molecular dynamics (MD) simulations. Results The full-length CDS of Labeo rohita STAT1a (LrSTAT1a) transcript consisted of 3238 bp that encoded a polypeptide of 721 amino acids sequence was identified. Phylogenetic analyses were performed based on the nucleotide sequences. Based on our findings, other vertebrates share a high degree of conservation with STAT1a. Additionally, we report that the in vivo immune stimulant poly I: C treatment of various tissues resulted in the expression of LrSTAT1a as determined by quantitative real-time polymerase chain reaction (qRT-PCR). In the current investigation, treatment with poly I: C dramatically increased the expression of LrSTAT1a in nearly every organ and tissue, with the brain, muscle, kidney, and intestine showing the highest levels of expression compared to the control. We made a 3D model of the STAT1a protein by using close structure homologs that were already available in the database. The model was then checked using molecular dynamics (MD) simulations. Consistent with previous research, the MD study highlighted the significance of the STAT1a protein, which is responsible for Src homology 2 (SH2) recognition. An important H-bonding that successfully retains SH2 inside the STAT1a binding cavity was determined to be formed by the conserved residues SER107, GLN530, SER583, LYS584, MET103, and ALA106. Discussion This study provides molecular insights into the STAT1a protein in Rohu (Labeo rohita) and highlights the potential role of STAT1a in the innate immune response in fish. The high degree of conservation of STAT1a among other vertebrates suggests its crucial role in the immune response. The in-vivo immune stimulation results indicate that STAT1a is involved in the immune response in various tissues, with the brain, muscle, kidney, and intestine being the most responsive. The 3D model and MD study provide further evidence of the significance of STAT1a in the immune response, specifically in SH2 recognition. Further research is necessary to understand the specific mechanisms involved in the IFN pathway and the role of STAT1a in the immune response of IMC.